(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
The processors are all important components of computer architecture. Computer architecture is a specification that describes how hardware and software technologies are connected to create a computer platform. It refers to a system that processes any fetched instruction. There are many different types of processors, and we shall examine the distinctions between single cycle and multi-cycle processors in this article. Former processors only executed an instruction in a single clock cycle, while multi-cycle processors disassembled the instructions into multiple functional pieces and then executed each portion in a separate clock cycle. Because the multicycle processor breaks down each instruction into smaller pieces, the amount of hardware required is decreased, and several registers are added to store data that may be utilized in the execution of subsequent instructions. A multicycle processor executes instructions in smaller clock cycles than a single cycle processor, according to the proposed study.